CALCULATION OF SULFUR ISOTOPE FRACTIONATION IN SULFIDES - Li Y.; Liu J. (My University, 2006)
The increment method has been successfully applied to calculate thermodynamic isotope fractionation factors of oxygen in silicates, oxides, carbonates, and sulfates. In this paper, we modified the increment method to calculate thermodynamic isotope fractionation factors of sulfur in sulfides, based on chemical features of sulfur-metal bonds and crystal features of sulfide minerals. To approximate the bond strength of sulfides, a new constant, known as the Madelung constant, was introduced. The increment method was then extended to calculate the reduced partition function ratios of sphalerite, chalcopyrite, galena, pyrrhotite, greenockite, bornite, cubanite, sulvanite, and violarite, as well as the isotope fractionation factors between them over the temperature range from 0 to 1000°C. The order of 34S enrichment in these nine minerals is pyrrhotite < greenockite < sphalerite < chalcopyrite < cubanite < sulvanite < bornite < violarite < galena. Our improved method constitutes another model for calculating the thermodynamic isotope fractionation factors of sulfur in sulfides of geochemical interest. ? 2006 Elsevier Inc. All rights reserved.
Keywords: ISOTOPIC FRACTIONATION; SULFIDE; SULFUR ISOTOPE; THERMODYNAMICS